2012
DOI: 10.1590/s0100-40422012000600010
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids and a neolignan glucoside from Guarea macrophylla (Meliaceae)

Abstract: Recebido em 7/8/11; aceito em 11/1/12; publicado na web em 15/5/12 This work describes the phytochemical study of the methanol extract obtained from leaves of Guarea macrophylla, leading to the isolation and identification of three flavonoid glycosides (quercetin 3-O-b-D-glucopyranoside, quercetin 3-O-b-D-galactopyranoside, kaempferol 7-O-b-D-glucopyranoside) and a neolignan glucoside, dehydrodiconiferyl alcohol-4-b-D-glucoside. All compounds were identified by a combination of spectroscopic methods ( 1 H, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 14 publications
5
28
0
Order By: Relevance
“…The 1 3 C-NMR data obtained from the current study were collected in dimethylsulfoxide-d6, and those published previously were in dimethylsulfoxide-d6 position 1 3 C-NMR data obtained from the current study collected in dimethylsulfoxide-d6/ ppm C-NMR data of F3 with the data published previously [9]. The 1 3 C-NMR data obtained from the current study were collected in dimethylsulfoxide-d6, and those published previously were in methanol-d4 position 1 3 C-NMR data obtained from the current study collected in dimethylsulfoxide-d6/ ppm A comparison of the 13 C-NMR data of F1 with the data published previously [11] was listed in Table 3. Previously, we have demonstrated that the EA/EuH fraction exhibited anti-metastatic activity by suppressing MMP-9 mRNA expression in MDA-MB-231 breast cancer cells [1].…”
Section: Resultssupporting
confidence: 51%
“…The 1 3 C-NMR data obtained from the current study were collected in dimethylsulfoxide-d6, and those published previously were in dimethylsulfoxide-d6 position 1 3 C-NMR data obtained from the current study collected in dimethylsulfoxide-d6/ ppm C-NMR data of F3 with the data published previously [9]. The 1 3 C-NMR data obtained from the current study were collected in dimethylsulfoxide-d6, and those published previously were in methanol-d4 position 1 3 C-NMR data obtained from the current study collected in dimethylsulfoxide-d6/ ppm A comparison of the 13 C-NMR data of F1 with the data published previously [11] was listed in Table 3. Previously, we have demonstrated that the EA/EuH fraction exhibited anti-metastatic activity by suppressing MMP-9 mRNA expression in MDA-MB-231 breast cancer cells [1].…”
Section: Resultssupporting
confidence: 51%
“…The anomeric proton H-1 at δH 5.46 showed a long-range correlation with signal at δC 133.3 (C-3) of the quercetin aglycon, indicating that the β-Dglucopyranosyl moiety connected to C-3 of the aglycon. The above data and comparison with those in the literature [4,5,6] allowed to identify 3 as quercetin 3-O-β-D-glucopyranoside (or isoquercetin).…”
Section: Resultsmentioning
confidence: 67%
“…Subfraction e8′ (1.472 g) was submitted to CC using CHCl 3 -MeOH (3:1), ten subfractions were obtained (e1″-e10″) and subfraction e3″ yielded compound 3 (330.1 mg, 1.6%). Quercetin-3-O-β-d-galactoside (2): yellow powder; IR (ATR, cm −1 ): 3270,2963,1656,1606,1504,1342,1171,1078,1021; NMR spectral data are in accordance with Pereira et al (2012).…”
Section: Extraction and Isolationmentioning
confidence: 63%
“…A recent study identified three new jacaranone derivatives from aerial parts of Senecio chrysanoides that presented cytotoxic activity (Wu et al 2015). The known compounds ( Figure 1) were identified as quercetin-3-O-β-d-galactoside (2), verbascoside (3) and polystyrene (4) by comparison with their NMR data with literature reports (Pham et al 1991;Schlauer et al 2004;Pereira et al 2012). Compound 2 is also known as hyperoside and it has been isolated from Jacaranda decurrens leaves (Blatt et al 1998), while compound 3 (1.6% of etOH extract) was previously identified from the hydroalcoholic extract of J. mimosifolia leaves (Moharram & Marzouk 2007).…”
Section: Chemical Characterisationmentioning
confidence: 81%